Hypofractionated stereotactic radiotherapy using coplanar VMAT for single small brain metastasis: dosimetric analysis and clinical outcomes - Lai, Jialu; Li, An; Zeng, Xianhu; Liu, Jia; Zhou, Lin (Frontiers in Oncology, 2025)
PurposeTo evaluate the dosimetric parameters and clinical outcomes of hypofractionated stereotactic radiotherapy (HSRT) for small brain metastases [BMs; planning target volume (PTV) ≤ 4 cm3) via coplanar volumetric modulated arc therapy (C-VMAT).MethodsBetween March 2019 and February 2023, 68 patients with a single BM treated with Linac-based HSRT (24–39 Gy in three fractions) via C-VMAT and a 3-mm PTV margin were enrolled in this retrospective analysis. A frameless head–neck–shoulder thermoplastic mask, whose immobilization accuracy is inferior to that of specialized mask fixation systems, was used to immobilize patients. Dosimetric parameters and clinical outcomes were evaluated.ResultsC-VMAT provided clinically satisfactory treatment plans, with median gradient index, conformity index, homogeneity index, and PTV coverage values of 4.30, 1.05, 1.28, and 98%, respectively. The median volumes of normal brain tissue receiving 18 Gy, 21 Gy, and 23 Gy were 7.29 cm3, 5.33 cm3, and 4.40 cm3, respectively. High delivery accuracy was observed, with a gamma passing rate ≥90% for all plans. As of June 2023, the median follow-up time was 9.1 months. The intracranial objective response rate and disease control rate were 64% and 96%, respectively. The median intracranial progression-free survival was 26.9 (95% CI, 12.7–41.1) months. The 1- and 2-year local control (LC) rates were 91.5% (95% CI, 80.1%–100%) and 83.2% (95% CI, 64.6%–100%), respectively. The 1- and 2-year intracranial control rates were 70.9% (95% CI, 55.2%–86.6%) and 51.2% (95% CI, 32.6%–69.8%), respectively. Only four irradiated lesions progressed at the end of follow-up. The cerebral radiation necrosis rate of all patients was 7.4%.ConclusionC-VMAT HSRT combined with a 3-mm PTV margin is an effective and safe treatment modality for small BMs.